Desarrollo de una propuesta de recuperación de residuos de solventes en la empresa Golden Flex S.A. (2017)
The present work of degree aims to develop a separation alternative to solve the problem of solvent waste management generated in the printing process in the company Golden Flex S.A, which also seeks the economic viability of the selected method. Based on the above the degree project is developed over 5 main chapters, in the first of them presents the theoretical framework regarding the inks and organic solvents together with the current legal framework for these substances; The second chapter contains the diagnosis made, which includes the raw materials (solvents) involved in the printing operation, the characterization of the solvent residue and the general description of the process, evidenced in the production history and payment supports; The third chapter contains the separation alternatives, the criteria, the selection matrix used taking into account the methodology of Kepner Tregoe; The fourth chapter covers the design with technical specifications of the selected alternative; In the last chapter emphasis is placed on investment costs or Capex and the costs of operations to evaluate the cost of the alternative.